AB1114-HPR Biologic Dose Tapering Improves Patient Care and Advances The Rheumatology Service. (15th July 2016) - Holloway, C.; Robinson, H.; Rees, D.; McDowell, J.; Andrews, S.; Joshi, A.; Jolliffe, V.; Trickey, J.; Peall, A.
Abstract : Background: Wye Valley NHS Trust has approximately 500 rheumatology patients on biologic therapy, with an annual growth rate of over 15%, increasing the clinical, administrative and financial burden to both the trust and commissioners. Evidence regarding the success of biologic dose tapering in rheumatoid arthritis (RA) patients in remission is emerging 1 . Savings generated by dose tapering can be shared between the provider and commissioner. We discuss the development of a dose tapering gain share which benefits the patient, provider and commissioner. Objectives: The aim was to develop an evidence based protocol for tapering of biologic drugs and to embed the protocol in clinical practice, benefitting patients by reducing their biologic therapy without adversely affecting their arthritis. The savings generated would fund the project including a biologics pharmacist, co-ordinator, consultant time, IT support and ultrasound equipment. To achieve this, the Clinical Commissioning Group (CCG) was to be approached to establish a gain share agreement. Methods: A gain share was agreed with the CCG. The initial savings would fund the cost of the project whilst the remainder would be split 50:50 in the first year, 60:40 in the second year and 70:30 in the subsequent three years, between the CCG and Trust respectively. A literature review was undertaken to devise an evidence-based dose tapering protocol for RA patients. The protocol also specified that ankylosing spondylitis (AS) and psoriatic arthritis (PsA) patients' biologics could be tapered at the discretion of the clinician, as there is currently a lack of evidence in these diseases. Eligible patients were identified and their doses tapered according to the protocol. Outcomes were recorded on a database, from which we extracted clinical and financial information. Results: After the first 8 months of dose tapering, 25 RA, 4 PsA and 3 AS patients' doses have been tapered. Only 2 RA patients (8%) so far have resumed their original doses due to disease flares. This indicates that we are likely to generate the savings required to fund the project. Importantly we have been able to reduce the medication burden of patients, hence reducing adverse effects whilst retaining disease control. There have also been fewer day case infusions, increasing the availability for day case treatments for other patients and reducing trust expenditure. In addition the project has enhanced the department's relationship with the CCG. Conclusions: This innovative project in a district general hospital demonstrates that savings from a dose tapering gain share can enhance and support an expanding biologics service. Initial results suggest that biologic doses can be successfully tapered in the majority of patients, whilst maintaining remission, with original doses reinstated for small numbers thus far. Further studies are required to assess long term outcomes. The team working exhibited by the rheumatology department and the CCG was essential for the success of the project. References: JS Smolen, R Landewé, F C Breedveld, M Buch, G Burmester, M Dougados, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs: 2013 update. Ann Rheum Dis, vol. 73, p. 492–509, 2014. Disclosure of Interest: None declared